PENEGAKAN SANKSI DISIPLIN TERHADAP ANGGOTA POLRI YANG MELAKUKAN PELANGGARAN DALAM MENJALANKAN TUGAS DI BIDANG PENEGAKAN HUKUM - , MASRI ADAM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine, to analyze and to explain the efforts of the police to prevent a breach of discipline against members of the Indonesian polices to conduct the law enforcement duties and to determine, to analyze and to explain the discipline of law enforcement the Indonesian polices who commit disciplinary offenses to run the law enforcement duties. The method used in this study is a normative legal research and empirical legal research. In the normative legal research materials research literature relating to the enforcement of disciplinary actions against members of the police who commit breaches of duty in the field of law enforcement. Then proceed with the empirical legal research study of primary data through direct interviews with sources who is competent, relevant to the problem under study. The data obtained are processed and analyzed using qualitative descriptive methods. Based on the research results, the polices effort to prevent breaches of discipline against the Indonesian polices to run law enforcement duties are the legal guidance to the Indonesian polices, psychic and spiritual guidance and oversight to the type of supervision, among others: direct supervision is the monitoring conducted by the supervisor directly, indirect supervision is through reports or information from the public or media. The law enforcement discipline against the Indonesian polices who violate the discipline to run the law enforcement duties, basically, the solution process refers to the Government Regulation 2 of 2003 concerning the discipline rules for the Indonesian polices and the Decision of the Chief of the Republic Indonesian Police numbers 43 of 2004 on the mechanism of disciplinary hearings for the Indonesian polices. The police sanctions for members who violate discipline in carrying out tasks in the field of law enforcement, referring to Article 9 Government Regulation 2 of 2003 on police discipline regulations. In the case of members of the police who committed the crime of speaking, the process is completed first in the general court, after the verdict is final and binding and then conducted a disciplinary hearing process.